Knowledge of and Attitudes Toward Hearing Loss Among Primary Care Physicians in the Public Health Sector of Mauritius - Foondun, Taslima; Pottas, Lidia; Soer, Maggi (International Archives of Otorhinolaryngology, 2023)
Introduction Primary care physicians are essential first points of contact for patients with hearing loss. Thus, knowledge of hearing loss and related aspects is essential to ensure the optimal management of individuals with suspected hearing loss.Objective This study aimed to determine the knowledge of and attitudes toward hearing loss among primary care physicians in the public health sector in Mauritius.Methods In this cross-sectional descriptive cohort study, 320 primary care physicians completed an online questionnaire adapted from previous questionnaires on knowledge of and attitudes toward hearing loss. Responses were analyzed using descriptive statistics and cross-sectional analyses.Results Primary care physicians showed limited knowledge of hearing loss in areas such as early identification and intervention, professionals responsible for hearing assessments, and hearing tests used for assessing hearing sensitivity. However, the responses also showed positive attitudes toward hearing loss. Significant associations between knowledge of and attitudes toward hearing loss were obtained regarding the type of physician, length of practice, and department posted in. Ear, nose, and throat specialists, as well as pediatricians, demonstrated significantly higher scores for both knowledge of and positive attitudes toward hearing loss.Conclusions The findings highlight a strong need for ongoing medical education to spread awareness about hearing loss among primary care physicians in the public health sector of Mauritius.
Keywords: primary care physicians; public health sector; hearing loss; knowledge; attitudes